Study of matrix converter based unified power flow controller applied PI-D controller - Motoyama, K.; Hanamoto, T.; Yamada, H.; Mailah, Nashiren Farzilah; Misron, Norhisam (School of Engineering, Taylor’s University College, 2014)
In this paper, the Unified Power Flow Controller (UPFC) using a matrix converter is studied. It is an adaptation of an approximate differentiation type PI-D controller. By setting appropriately the values of the gain controller, it is possible to stabilise the power of the transmission line by controlling the UPFC by a matrix converter. The matrix converter is a power conversion circuit that can convert an arbitrary phase and amplitude of the AC power directly to AC power. The principle of creating a switching pattern that adopts a Direct Duty ratio Pulse Width Modulation (DDPWM) scheme. The UPFC is a stationary device to adjust the grid voltage for controlling the power flow is inserted into the power system, and controls the transmission power according to the load variations. This is intended to stabilise the power system. Verification is done by simulation using MATLAB/Simulink for the validity of this proposed method.